Religion and Mental Health: A Review of Antoine Vergote's Approach in Guilt and Desire - O'Connor, Kathleen V. (The international journal for the psychology of religion, 1998)
The work of Antoine Vergote, though widely publicized, is little known outside Europe. Using Vergote's best known book, Guilt and Desire, this article presents a synopsis of his thinking. These feelings, guilt and desire, are considered to be at the core of human experience. Religious faith and mental health incorporate the tension that guilt and desire evoke. The article considers the internal, as well as cultural dynamics involved in affirming and directing these dominant life forces.